Pentagon Fraud’s Determinants on Fraudulent Financial Statement: Whistleblowing as Moderating Variable in Soes - Rania Suksmaningtyas; Imang Dapit Pamungkas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study examines the impact of Pentagon Fraud factors on FSF, with WBS as a moderation variable, focusing on Indonesian State-Owned Enterprises (SOEs) from 2021 to 2024. The Pentagon’s Fraud Theory encompasses five key elements: pressure, opportunity, rationalization, competence, and arrogance, each of which is represented by financial stability, ineffective monitoring, the quality of auditors, the experience of directors, and CEO pictures. This study aims to determine how these factors affect financial reporting that contains fraud, and whether WBS can strengthen or weaken the relationship between the two. Using a quantitative approach with secondary data from the annual reports of 104 SOEs, thisi study applied panel data regression method. FSF was measured using the Beneish M-Score, while the effect of moderation was tested through moderated regression analysis. The results of this study are expected to provide deeper insights into the dynamics of fraud in the public sector and highlight the importance of WBS as a governance tool in reducing the risk of fraud. The study contributes to the previous literature by integrating a comprehensive fraud framework and testing it with moderation mechanisms, while also focusing on specific institutional contexts (SOEs), which have not been explicity explored in previous studies.